2018
DOI: 10.1002/ange.201712726
|View full text |Cite
|
Sign up to set email alerts
|

Direct N‐Glycofunctionalization of Amides with Glycosyl Trichloroacetimidate by Thiourea/Halogen Bond Donor Co‐Catalysis

Abstract: Using ah alogen bond (XB) donor and Schreiners thiourea as cooperative catalysts,various amides,including the asparagine residues of several peptides,w ere directly coupled with glycosyl trichloroacetimidates to give unique N-acylorthoamides in good yields.S ynthetic applications of N-acylorthoamides,including rearrangement to the corresponding b-Nglycoside,were also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 82 publications
1
6
0
Order By: Relevance
“…To our delight, gold catalyzed glycosidation was found to be suitable for the direct attachment of the asparagine derivative 6 a emulating the biosynthetic machinery of N ‐linked glycoprotein synthesis. The protected asparagine Cbz⋅Asn⋅OBn ( 10 ) produced the N ‐linked asparagine ribofuranoside 11 a in 75 % yield within 3 h directly without any formation of the 1,6‐anhydro sugar [9b] or the orthoamides as reported earlier [9c] . Identification of these silver‐assisted gold‐catalyzed N ‐glycosidation conditions for the model ribofuranosides 1 a → 4 a , 7 a , 9 a , 11 a motivated us to investigate the scope of these glycosidation conditions for the synthesis of a range of N ‐glycosides.…”
Section: Figuresupporting
confidence: 55%
“…To our delight, gold catalyzed glycosidation was found to be suitable for the direct attachment of the asparagine derivative 6 a emulating the biosynthetic machinery of N ‐linked glycoprotein synthesis. The protected asparagine Cbz⋅Asn⋅OBn ( 10 ) produced the N ‐linked asparagine ribofuranoside 11 a in 75 % yield within 3 h directly without any formation of the 1,6‐anhydro sugar [9b] or the orthoamides as reported earlier [9c] . Identification of these silver‐assisted gold‐catalyzed N ‐glycosidation conditions for the model ribofuranosides 1 a → 4 a , 7 a , 9 a , 11 a motivated us to investigate the scope of these glycosidation conditions for the synthesis of a range of N ‐glycosides.…”
Section: Figuresupporting
confidence: 55%
“…[42,43] Though, rearrangement of trichloroacetimidates to trichloroacetamides is a known side reaction. [44] A working hypothesis that could explain this anomerization is that after protonation and formation of an oxocarbenium ion-like intermediate, the acceptor will not be in a favourable trajectory for attack of the anomeric carbon (Figure 4). Whereby reattachment of the amide becomes a competing pathway.…”
Section: P E R S O N a L A C C O U N T T H E C H E M I C A L R E C O R Dmentioning
confidence: 99%
“…Ribonucleoside syntheses are similarly well established, where typical methods utilize either a Lewis acid‐mediated (TiCl 4 ) chlorination of 1‐O‐acetyl‐2,3,5‐tri‐O‐benzoyl‐β‐ D ‐ribofuranose (Harki et al., ) or utilize intermediates 5 (Kane & Mann, ; Stewart & Williams, ) and 6 (Rosemeyer & Seela, ; Ugarkar et al., ; Wilcox & Otoski, ). We found that displacement of 1‐chloro‐2,3,5‐tri‐O‐benzoyl‐β‐ D ‐ribofuranose with the sodium salt of 4CI yielded what is likely a trapped amide acetal intermediate indicating a lack of nucleophilicity and thus did not produce the desired coupling product (see Kobayashi, Nakatsuji, Li, Tsuzuki, & Takemoto, and Sokolova, Shevchenko, & Preobrazhenskaya, for examples of such structures). We therefore chose to use the 5 / 6 sequence.…”
Section: Commentarymentioning
confidence: 99%